2018
DOI: 10.12688/f1000research.12028.1
|View full text |Cite
|
Sign up to set email alerts
|

The role of NAFLD in cardiometabolic disease: an update

Abstract: Non-alcoholic fatty liver disease (NAFLD) is the most common cause of chronic liver disease in the world, yet the complex pathogenesis remains to be fully elucidated. The prevalence of NAFLD has risen precipitously in recent years and is now a leading indication for liver transplantation. New waitlist registrants with non-alcoholic steatohepatitis–induced cirrhosis increased by 170% from 2004 to 2013. In addition, patients with NAFLD are at increased risk of both cardiovascular disease and type II diabetes. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 54 publications
1
16
0
2
Order By: Relevance
“…Non-alcoholic fatty liver disease (NAFLD) represents the most common cause of chronic liver disease in developed countries worldwide [1,2]. NAFLD is considered to be the hepatic manifestation of the metabolic syndrome [3].…”
Section: Introductionmentioning
confidence: 99%
“…Non-alcoholic fatty liver disease (NAFLD) represents the most common cause of chronic liver disease in developed countries worldwide [1,2]. NAFLD is considered to be the hepatic manifestation of the metabolic syndrome [3].…”
Section: Introductionmentioning
confidence: 99%
“…Chronic hypoxia has been identified as a major contributor to liver injury as a response to obstructive sleep apnea (OSA) . This has been to the cardio metabolic syndrome and NAFLD . A study on mice by Savransky et al found that chronic intermittent hypoxia when combined with a high‐fat diet (HFD) induced inflammation and lipid peroxidation, with the hypoxia exposure group showing increased steatosis .…”
Section: Introductionmentioning
confidence: 99%
“…1 The prevalence of NAFLD has markedly increased over the last years, concomitantly with increases in the prevalence of both obesity and the metabolic syndrome. 2 The global prevalence of NAFLD is currently estimated to be 25% with the highest prevalence in the Middle East and South America and the lowest in Africa. 3 Using an elevated fatty liver index (FLI), a validated proxy of NAFLD, 4,5 a similar prevalence of NAFLD was reported in a large North European cohort.…”
Section: Introductionmentioning
confidence: 99%